IMITATION MODEL OF DEVELOPING RETAIL NETWORK ON THE PLATFORM IBM COGNOS TM1 - Vyacheslav V. Nefedov; Olga V. Kitova; Andrey V. Starovoytov (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The authors developed a stimulator of the retail network on the platform IBM Cogcos TM1 meant for research and design of the system of supporting decision-making. The article describes the imitation model of the retail market being a part of the stimulator. Modeling is done for the system consisting of optional number of regions, retail networks available in all regions, three formats of shops which differ in areas and product range and three groups of products. The demand model by Gold/Prey provides an opportunity to model decision-making about the number of shops being opened in various regions and about the trade make-up depending on the assumption concerning competitiveness of shops in the network. The model includes dynamics of demand, prices and costs of marketing, it is parametric and provides serious results with a wide range of income data due to principles of system dynamics, sigma-shaped functions of market response and some additional eristic described in the article.